Cross-National Analysis of Construction Project Cost Overruns: Risk Factors, Contractual Governance, and Mitigation Strategies - Lande, Shubham Uttam; Chandekar, Pratibha (Journal of Progress in Civil Engineering, 2025)
This research examines cost overruns in the construction industry by comparing Bahrain Strategic Road Master Plan (SRMP) with the construction sector of Australia and Malaysia. Key causes include inaccurate estimates, design changes, execution delays and economic fluctuations. The study highlights the role of risk management, stakeholder engagement, and advanced technologies such as Building Information Modeling (BIM) in mitigating cost overruns. Through a comprehensive analysis, the research provides insights into practices for improving cost estimation and project execution across the three regions, contributing to construction sustainability and economic growth.